2005
DOI: 10.1177/152692480501500407
|View full text |Cite
|
Sign up to set email alerts
|

Social Work Interventions with Living Related Liver Donors: The Implications for Practice

Abstract: Living related liver donations are increasingly used to address the lack of organs available to patients faced with end-stage liver disease. A significant need exists for enhanced psychosocial intervention for donors. We sought to explore donor reactions by assessing psychosocial issues after donation. A descriptive review of donors was undertaken. The overall incidence of psychosocial issues after donation was examined by using a uniform interview questionnaire and by anecdotal case studies. Responses tend to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
3
2
0
Order By: Relevance
“…Moreover, no donor responded that live liver donation should be abandoned or they felt "forced" to donate, and all donors were satisfied with their donation decision and felt empowered and glad for the donation and saving the life of beloved ones. is is in accordance with the findings of a number of studies [2,5,7,10].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, no donor responded that live liver donation should be abandoned or they felt "forced" to donate, and all donors were satisfied with their donation decision and felt empowered and glad for the donation and saving the life of beloved ones. is is in accordance with the findings of a number of studies [2,5,7,10].…”
Section: Discussionsupporting
confidence: 93%
“…However, as men have pointed out better preparation, it may be necessary to offer an education campaign and sessions through the popular media to educate the general public about organ donation and what they can expect and engage the interdisciplinary advocacy team of donors before the donation process to overcome concerns raised at any time. With regard to pre-and postdonation support, this study found support from the transplant team, family, and friends, and this is similar to the literature that donors feel well supported from their environment [2,10,11].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Donor candidates should have a good understanding of the morbidity and mortality of living liver donation and confirm their voluntary participation, with the absence of coercion, before the donation decision is made via consultations with a transplant coordinator, social worker, psychiatrist, or donor advocate staff member. [912] Furthermore, the reasons for exclusion from the selection process should be recorded and analyzed to further improve donor quality of care. [3]…”
Section: Introductionmentioning
confidence: 99%